1989
DOI: 10.1164/ajrccm/140.5.1294
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cough as the Sole Presenting Manifestation of Gastroesophageal Reflux

Abstract: Nine patients complaining only of chronic cough of unknown cause were prospectively studied with prolonged esophageal pH monitoring (EPM) before and after cough had disappeared as a complaint in order to determine if and why gastroesophageal reflux (GER) was causing their coughs. Coughs disappeared as a complaint an average of 161 +/- 75 days after medical therapy for GER. Comparisons of pretreatment and post-treatment EPM data revealed the following: numbers of coughs (p = 0.029), total refluxes (p = 0.001), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
96
0
10

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(111 citation statements)
references
References 6 publications
5
96
0
10
Order By: Relevance
“…Additionally, esophageal pH monitoring may be the only method of diagnosing GER in up to 32% of patients with reflux-induced cough (29). As symptoms of GER, such as heartburn, are frequently absent in patients with reflux-induced cough (21,30), therapeutic trials may be less useful if no symptoms of GER are present. The ReQuest is a valid and reliable tool for measuring GER symptoms (15), but other methods are required for the objective assessment of symptom severity and patient response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, esophageal pH monitoring may be the only method of diagnosing GER in up to 32% of patients with reflux-induced cough (29). As symptoms of GER, such as heartburn, are frequently absent in patients with reflux-induced cough (21,30), therapeutic trials may be less useful if no symptoms of GER are present. The ReQuest is a valid and reliable tool for measuring GER symptoms (15), but other methods are required for the objective assessment of symptom severity and patient response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…cough goes away after specific therapy aimed at its cause) was not utilized at the inclusion. Secondly, it has been shown that GOR can be the cause of chronic cough even when the conventional variables in the pH monitoring are normal, if the cough is associated with a reflux episode [6]. Since we wanted to be certain that all the patients who were randomized really had GOR, these traditional variables were used to classify the patients.…”
Section: Discussionmentioning
confidence: 99%
“…This increase was largely prevented by the tachykinin NK 1 and NK 3 receptor antagonists SR 140333 and SR 142801 (1-10 mg?kg -1 ). These results suggest that protein extravasation in the airways, as induced by intraoesophageal HCl infusion, is mainly dependent on the release of tachykinins, and that both NK 1 Gastro-oesophageal reflux is a common clinical disorder associated with a variety of respiratory symptoms, including chronic cough and bronchoconstriction [1][2][3][4]. It has been shown to be more frequent in people with asthma [4].…”
mentioning
confidence: 94%